Anthropometry, Body Composition and Resting Energy Expenditure in Human - Tur, Josep A. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Data on nutritional status of human populations are periodically needed, as well as their relationships with anthropometry, body composition, body image and energy expenditure, and also with health lifestyle outcomes. All these parameters contribute jointly to give a complete knowledge on dietary and lifestyle habits, and hence how to proceed to improve it in order to enjoy an optimal healthy status. So, you are kindly invited to submit proposals for manuscripts that fit the objectives and the topics of this Nutrients Special issue.The aim of this proposed Nutrients Special Issue on ""Anthropometry, Body Composition and Resting Energy Expenditure in Humans"" is to publish selected papers detailing specific aspects of anthropometric, body composition and energy expenditure data in human populations and their relationships with nutritional status, as well as nutritional surveys and trials that examine measured differences or changes in these parameters are also cordially invited.